Prevalence and impact of chronic ankle instability in female sport: a cross-sectional study - Forsyth, L.; Donovan, L.; Martin-Smith, R.; Rowe, P. L. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background The prevalence and impact of chronic ankle instability (CAI) is underreported among females participating in sports that are considered high risk for lateral ankle sprains. Identifying the prevalence and contextualising the impact may help reinforce the necessity of targeted rehabilitation and injury risk reduction strategies. The primary aim was to conduct an international study identifying the prevalence of CAI and impact on ankle function and quality of life of females participating in high-risk sports.